Musa sebagai Teladan dalam Menanamkan Iman bagi Generasi Z - Naha, Melviani Konga; Sose, Oktoviana; Bambangan, Malik (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article explores the exemplary life of Moses in the Old Testament as an inspiration for Generation Z in nurturing and sustaining their faith amidst the challenges of the digital era. As a spiritual leader and bearer of God's law, Moses exemplified obedience, courage, and faith-based leadership—values that remain relevant for today’s youth. Through significant events in his life such as the burning bush encounter, the Exodus, and the wilderness journey, Moses emphasized the importance of trusting God and living according to His commandments. The article also highlights the role of the family, particularly fathers, in providing spiritual education, as well as the necessity for continuous and contextually relevant faith education. By emulating Moses, Generation Z is encouraged to develop strong faith, maintain hope in God, and face societal pressures and life uncertainties with resilience and spiritual conviction.